2017
DOI: 10.1002/ange.201703235
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Boroauride: A Donor–Acceptor Complex of Anionic Gold

Abstract: Gold is unique among the transition metals in that it is stable as an isolated anion (auride). Despite this fact, the coordination chemistry of anionic gold is virtually nonexistent, and this unique oxidation state is not readily exploited in conventional solution chemistry owing to its high reactivity. Through the use of a new molecular scaffold based on diboraanthracene (B2P2, 1), we have overcome these issues by avoiding the intermediacy of zerovalent gold and stabilizing the highly reduced gold anion throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The 12-electron auride anion is typically generated by the reduction of metallic gold with alkali metals, to give salts such as CsAu and RbAu 11,12 ; the solution chemistry of these salts, however, is restricted to liquid ammonia 13,14 .Reduction of organometallic gold compounds to give systems in low oxidation states (i.e. zero or below) has been attempted, but with limited success [15][16][17][18][19][20] . Thermodynamics typically drive the aggregation of molecular Au(0) systems to clusters of colloidal gold [15][16][17][18] .…”
mentioning
confidence: 99%
“…The 12-electron auride anion is typically generated by the reduction of metallic gold with alkali metals, to give salts such as CsAu and RbAu 11,12 ; the solution chemistry of these salts, however, is restricted to liquid ammonia 13,14 .Reduction of organometallic gold compounds to give systems in low oxidation states (i.e. zero or below) has been attempted, but with limited success [15][16][17][18][19][20] . Thermodynamics typically drive the aggregation of molecular Au(0) systems to clusters of colloidal gold [15][16][17][18] .…”
mentioning
confidence: 99%
“…The chemistry of gold compounds bonded to main group elements has been developed extensively. 7,[18][19][20][21] Very recently, a nucleophilic gold complex I released by Goicoechea, Aldridge and colleagues (Chart 1), was employed rstly in the activation of CO 2 and carbodiimide unfolding an unprecedented nucleophilicity of auride complex. 20 The umpolung reactivity of gold was ascribed to its high polarization of Au-Al bond.…”
Section: Full Textmentioning
confidence: 99%
“…The chemistry of gold compounds bonded to main-group elements has been developed extensively in recent years 3 7 . Goicoechea, Aldridge and coworkers have reported that novel gold-aluminum complex I (Fig.…”
Section: Introductionmentioning
confidence: 99%